Enhancing Junior High School Teachers ‘Capacity in Educational Problem-Solving: An Evaluation of a Design-Based Research Workshop - Wigati, Fikri Asih (Journal of Educational Sciences, 2025)
This study evaluates the effectiveness of a Design-Based Research (DBR) workshop in enhancing junior high school teachers' capacity to address educational problems. A four-day workshop was attended by 20 teachers from 5 junior high schools in a sample city. Mixed methods were used to analyze workshop outcomes, including pre-post surveys, analysis of mini DBR proposals, semi-structured interviews, and longitudinal follow-ups. Results show significant improvement in teachers' understanding and skills related to DBR. The workshop produced 15 mini DBR proposals ready for implementation. Key challenges included time constraints for data analysis, variation in participants' initial understanding, and concerns about institutional support. A three-month follow-up revealed that 60% participants had initiated DBR projects in their schools. This study highlights the potential of DBR workshops in enhancing research-based practices in schools and recommends strategies for sustainable implementation. The follow-up survey revealed that 60% of participants had initiated DBR projects in their schools within three months of the workshop. The analysis of the DBR implementation revealed several critical factors that contributed to successful outcomes, as well as certain barriers that posed challenges to the implementation process.